The Effectiveness of the Group Tutoring Service Model Based on "Ngapak" Cultural Listing to Increase Character Values in Students at SD Negeri 2 Purbalingga Lor - Basuki, Agus; Wulansari, Raini Retno (Jurnal Prima Edukasia, 2024)
The aim of this research is to determine the effectiveness of group guidance based on cultural literacy "Ngapak" to improve character values in students at SD Negeri 2 Purbalingga Lor. This type of research is quantitative research with experimental methods. One group pretest-posttest research design. The population of this study was class VI students at SD Negeri 2 Purbalingga Lor classes VI A and VI B, totaling 50 students. The research sample consisted of 8 students who were categorized as low in student character scores. The sample was determined based on a purposive sampling technique with an instrument used on a Likert scale. Test the validation of this research using product moments and rehabilitation tests using Cronbach's Alpha. Research analysis used the Wilcoxon test with the help of SPSS 26 for Windows. The research results show a significant increase in students' character scores after participating in the cultural literacy-based group guidance program "Ngapak". This can be seen from the results of the experimental class pretest. From the pretest results, a score of 438 was obtained with an average score of 54.75. After being given service, students experienced an increase in their score on the Posttest by 770 with an average of 96.25. The results of the Wilcoxon test using SPSS 26 showed that the Z count in the experimental class was -2.527 and the significance level was 0.05. is 0.012<0.05, then Ho is rejected and Ha is accepted, meaning that there is a significant difference between the students' character scores after being given the "Ngapak" cultural literacy-based group guidance service model. Thus it can be concluded that the "Ngapak" cultural literacy-based group guidance service model is effective to increase the character scores of students at SD Negeri 2 Purbalingga Lor. This is proven by seeing the Posttest scores which have increased